2014
DOI: 10.1016/j.drugalcdep.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal cocaine exposure and age of sexual initiation: Direct and indirect effects

Abstract: Background Prenatal cocaine exposure (PCE) has been linked to child behavior problems and risky behavior during adolescence such as early substance use. Behavior problems and early substance use are associated with earlier initiation of sexual behavior. The goal of this study was to examine the direct and indirect effects of PCE on sexual initiation in a longitudinal birth cohort, about half of whom were exposed to cocaine in utero. Methods Women were interviewed twice prenatally, at delivery, and 1, 3, 7, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…That is, although PCE effects on early sexual initiation was observed for both boys and girls, its underlying mechanism was gender-dependent, indicating childhood externalizing behavior as a pathway only for girls. Our study is in line with two previous studies indicating a greater risk of early sexual initiation among PCE adolescents (De Genna et al, 2014; Lambert et al, 2013), despite methodological differences in operationalization of early sexual initiation and analytical approaches. A stronger relationship between externalizing behavior and early sexual initiation for girls than for boys was observed in our high risk sample, although large population-based studies identified childhood externalizing behavior as a risk factor regardless of gender (McLeod and Knight, 2010; Skinner et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That is, although PCE effects on early sexual initiation was observed for both boys and girls, its underlying mechanism was gender-dependent, indicating childhood externalizing behavior as a pathway only for girls. Our study is in line with two previous studies indicating a greater risk of early sexual initiation among PCE adolescents (De Genna et al, 2014; Lambert et al, 2013), despite methodological differences in operationalization of early sexual initiation and analytical approaches. A stronger relationship between externalizing behavior and early sexual initiation for girls than for boys was observed in our high risk sample, although large population-based studies identified childhood externalizing behavior as a risk factor regardless of gender (McLeod and Knight, 2010; Skinner et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…To date, three studies from two prospective cohorts have investigated the effects of PCE on adolescent sexual behavior (Conradt et al, 2014; De Genna et al, 2014; Lambert et al, 2013). First trimester PCE was a significant predictor of early sexual intercourse, with most PCE effects occurring between the ages of 13–18 when rates of initiation of sexual intercourse were approximately 10% higher among adolescents with PCE (De Genna et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strongest correlates of early sex is substance use (2). Correlation between early sexual onset and more frequent use of addictive substances were well documented in the systematic review of Zimmer-Gembeck and Helfand, which compared 35 studies on this topic (3).…”
Section: Introductionmentioning
confidence: 98%
“…Prenatal cocaine exposure (PCE) may increase the vulnerability for adolescent sexual risk behavior (De Genna et al, 2014; Lambert et al, 2013; Min et al, 2015). Approximately 214,000 infants are exposed in utero to illicit drugs, including cocaine, each year in the United States (Substance Abuse and Mental Health Services Administration (SAMHSA), 2014); however, the effects of PCE on adolescent sexual behavior have not been well-established, with only three published studies from three prospective birth cohorts to date (De Genna et al, 2014; Lambert et al, 2013; Min et al, 2015).…”
Section: Introductionmentioning
confidence: 99%